Distribution Of Helminth Infections In Gastro-Intestinal Tract Of Horses: Azhar Ali Faraj – Fawzia S.Khadim – Shehella R. Fadl - Faraj, Azhar Ali (The Iraqi Journal of Veterinary Medicine, 2007)
This study concerns with incidence of infection of gastro-intestinalhelminthes ( Nematode) in horses. Results revealed that the rate of parasitichelminthes was 50.54%. The peak of Nematode infection was 86.6% inSpring followed by 57.5% .during Autumn then the infection declined inSummer and Winter to 33.73% and 22.5% respectively Four genera ofparasitic nematodes were identified the highest rate of infection withStrongylus was recorded in horses 49.54% followed by Parascris 14.09%,the lowest infection with Trichostrongylus and Oxyuris was 9.09 % and7.72% respectively. Result revealed higher helminthes infections in females57.05% than in males 39.7%.